Why Is Reading Important? - G. Amirova (International Consortium of Education and Culture Research Studies, 2019)
The aim to write this article is to figure out the reasons why we should read, and giving all the advantages of itself. Moreover, social benefits of reading have been discussed by the author. To conclude with, research has been analyzed to get better development of the reading, importance, and benefits of it have been investigated.